Power quality enhancement of isolated power systems through series compensation - Wang, Tongxun (2008)
The use of series compensator (SC) in improving power quality of isolated power systems is considered in the thesis. For the upstream disturbances, the role of the compensator is to mitigate not only the effects of momentary voltage sags/swells, but also to control the level of harmonic distortions in the networks. The approach used is to extend the voltage injection scheme of the SC to incorporate load current feedback and an external inductive filter. Furthermore, it is shown that in the process of compensation, the SC exchanges energy with the external network. A control strategy for the SC is developed to regulate power flow. This is achieved through phase adjustment of load terminal voltage. It leads to an increase in the ride-through capability of loads to the voltage sags/swells. When a downstream fault occurs, the SC achieves the current limiting function by injecting a voltage component to restore the PCC voltage to its pre-fault phasor value.